Controlling Unmanned Surface Vehicle Using MQTT Protocol - Rachmad Andri Atmoko; Daoguo Yang; M Yayan Alfiani; Lilik Subiyanto (Information Technology and Science (ITScience), 2019)
Abstract- The communication system at USV is the most important part of ensuring that the USV control system runs well. Communication systems that are commonly used at USV are generally still local networks. The development of a wider range of communications is needed to improve USV scalability so that the benefits can be increased to support the concept of remote laboratory and remote surveillance. USV is generally controlled using a wireless network with a limited work area using WIFI or using another electromagnetic waves transmission. This research proposes the development control and monitoring systems of USV to be controlled over the Internet by using the message queuing telemetry transport(MQTT) Protocol. This idea makes the USV can be controlled remotely, no longer have to operate it in the field. The control speed response of rudder and motor are analyzed. Performance monitoring of the compass sensor, GPS, and cameras also showed good results. As a result, the average delay time generated is 1.6 second.